Environmental Factors Item Development for Persons With Stroke, Traumatic Brain Injury, and Spinal Cord Injury - Heinemann, Allen W. (Arch Phys Med Rehabil, 2013)
OBJECTIVES: To describe methods used in operationalizing environmental factors; to describe the results of a research project to develop measures of environmental factors that affect participation; and to define an initial item set of facilitators and barriers to participation after stroke, traumatic brain injury, and spinal cord injury. DESIGN: Instrument development included an extensive literature review, item classification and selection, item writing, and cognitive testing following the approach of the Patient-Reported Outcomes Measurement Information System. SETTING: Community. PARTICIPANTS: Content area and outcome measurement experts (n=10) contributed to instrument development; individuals (n=200) with the target conditions participated in focus groups and in cognitive testing (n=15). INTERVENTIONS: None. MAIN OUTCOME MEASURES: Environmental factor items were categorized in 6 domains: assistive technology; built and natural environment; social environment; services, systems, and policies; access to information and technology; and economic quality of life. RESULTS: We binned 2273 items across the 6 domains, winnowed this pool to 291 items for cognitive testing, and recommended 274 items for pilot data collection. CONCLUSIONS: Five of the 6 domains correspond closely to the International Classification of Functioning, Disability and Health taxonomy of environmental factors; the sixth domain, economic quality of life, reflects an important construct that reflects financial resources that affect participation. Testing with a new and larger sample is underway to evaluate reliability, validity, and sensitivity.